2012 IEEE/RSJ International Conference on Intelligent Robots and Systems 2012
DOI: 10.1109/iros.2012.6385503
|View full text |Cite
|
Sign up to set email alerts
|

Ground plane feature detection in mobile vision-aided inertial navigation

Abstract: Abstract-In this paper, a method for determining ground plane features in a sequence of images captured by a mobile camera is presented. The hardware of the mobile system consists of a monocular camera that is mounted on an inertial measurement unit (IMU). An image processing procedure is proposed, first to extract image features and match them across consecutive image frames, and second to detect the ground plane features using a two-step algorithm. In the first step, the planar homography of the ground plane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…For key frame extraction, if fast processing is required, method proposed by Raikwar et al [25] is the appropriate one as it requires very less time for extraction of key frames, where as if high accuracy and simplicity is considered then absolute distinction of histograms of successive frames method proposed by Sheena et al [26] comes out to be appropriate one. In ground plane detection phase, to determine ground plane features, kalman filter and outlier rejection approach proposed by Panahandeh et al [33] is concluded to be a good method. To detect obstacles from moving vehicles, novel image registration algorithm VOFOD by Molineros et al [32] is the appropriate one.…”
Section: Results and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…For key frame extraction, if fast processing is required, method proposed by Raikwar et al [25] is the appropriate one as it requires very less time for extraction of key frames, where as if high accuracy and simplicity is considered then absolute distinction of histograms of successive frames method proposed by Sheena et al [26] comes out to be appropriate one. In ground plane detection phase, to determine ground plane features, kalman filter and outlier rejection approach proposed by Panahandeh et al [33] is concluded to be a good method. To detect obstacles from moving vehicles, novel image registration algorithm VOFOD by Molineros et al [32] is the appropriate one.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…Algorithm also performed well when ground level in images was less. In 2012, Panahandeh et al [33] figured locomotion by executing an IMU (Inertial Measurement Unit) and ground level in the images was identified in 2 steps. 1 st on the basis of kalman-filter (nonlinear), planer homography was generated.…”
Section: Ground Plane Detectionmentioning
confidence: 99%
“…The ground plane features are selected using a predefined box in the lower part of the image while the outliers are rejected using the filters estimates over time. Detail studies about the ground plane feature detection and outlier removal are given in [31,32]. Time synchronization and temporal ordering between the IMU and the camera measurements are based on methods in [26].…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Segmenting the floor and detecting moving objects become significant tasks for guiding the robot within an environment [5], [6]. Specular reflections and textured floors are the main difficulties faced by floor segmentation algorithms [7].…”
Section: Motivationmentioning
confidence: 99%